Between Profit-Seeking and Prosociality: Corporate Social Responsibility as Derridean Supplement - Sabadoz, Cameron (2011)
This article revolves around the debate surrounding the lack of a coherent definition for corporate social responsibility (CSR). I make use of Jacques Derrida’s theorizing on contested meaning to argue that CSR’s ambiguity is actually necessary in light of its functional role as a “supplement” to corporate profit-seeking. As a discourse that refuses to conclusively resolve the tension between profit-seeking and prosociality, CSR expresses an important critical perspective which demands that firms act responsibly, while retaining the overall corporate frame of shareholder supremacy. CSR does this by ambivalently affirming both profit-seeking and prosociality, a necessary contradiction. Attempts to reduce CSR’s ambiguity can thus only succeed by undermining its viability as a normative discourse that captures how certain elements of society understand how firms should act. The analysis suggests that greater scholarly attention is needed with regard to the material discursive environments within which discourses such as CSR are deployed. A discursive approach to research could thus benefit future practitioners, who have to act according to fluid standards of responsibility that cannot be authoritatively defined, but which can be better understood than they are at present.
Keywords: Undecidability; Supplementarity; Jacques Derrida; Discourse; Différance; Corporate Social Responsibility